PENGARUH SISTEM PENGUKURAN KINERJA, SISTEM PENGHARGAAN TERHADAP KINERJA MANAJERIAL - Hany Indah Pratiwi; Novita Sari (JURNAL FAIRNESS, 2021)
This study aims to determine how the influence of the Performance Measurement System, the Reward System of PT.POS Indonesia, Bengkulu Province. There is a decrease in the competitiveness and quality of managers in improving the quality of PT POS INDONESIA.Using primary data obtained by distributing questionnaires to all financial managers. Data were analyzed using multiple regression analysis using the SPSS Statistics 24 program. The results of this study indicate that the Performance Measurement System and Rewards System of PT POS INDONESIA Bengkulu Province has a positive effect on managerial performance. Based on these results, this research can be used as material for consideration or suggestions for PT POS Indonesia Bengkulu Province in order to maintain its managerial quality in order to compete with other shipping services.